2019
DOI: 10.5753/jis.2019.717
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Protocol for fMRI Assessment Associated with Augmented Reality Rehabilitation of Stroke Subjects

Abstract: New technologies for rehabilitation involving Augmented Reality (AR) as a complement to conventional therapy have appeared in recent years. An earlier study for shoulder rehabilitation using the AR NeuroR computer system showed improved clinical outcomes for stroke patients. This study aims to analyze a proposed protocol to measure possible changes in functional brain connectivity associated with the use of the NeuroR system in the context of shoulder motor rehabilitation of post-stroke subjects. A pilot study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 35 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…Our result was similar to the findings of a recent study, which showed that use of a VR-based mirror training system was capable of improving hand performance significantly for young participants [40]. Recent evidence from neuroimaging shows that the functional brain connectivity for a patient was changed after receiving AR-based mirror training, through the examination of functional magnetic resonance imaging [41]. Either augmented or virtual reality is a computer-generated graphical environment that offers an immersive environment to affect engagement of the user.…”
Section: Discussionsupporting
confidence: 91%
“…Our result was similar to the findings of a recent study, which showed that use of a VR-based mirror training system was capable of improving hand performance significantly for young participants [40]. Recent evidence from neuroimaging shows that the functional brain connectivity for a patient was changed after receiving AR-based mirror training, through the examination of functional magnetic resonance imaging [41]. Either augmented or virtual reality is a computer-generated graphical environment that offers an immersive environment to affect engagement of the user.…”
Section: Discussionsupporting
confidence: 91%
“…The choice of keywords in this review was based on terms that best represented the topic of our interest. We also included two studies from our research group [33,34]. Out of the 50 collected manuscripts, 28 did not meet the eligibility criteria (see section 2.2) and were excluded.…”
Section: Overviewmentioning
confidence: 99%
“…Although in many cases specific VR equipment has been developed for rehabilitation purposes (e.g. [27][28][29][30][31][32][33][34][35][36]), some researchers have adapted or directly used already existing off-the-shelf video games [37][38][39], which are usually lower cost and more accessible. In VR rehabilitation, the user receives real-time feedback regarding his/her interaction with the environment and objects within.…”
Section: Introductionmentioning
confidence: 99%
“…Among the projects aimed at the creation and testing of new technologies for neurorehabilitation, the BRAINN_VR research line is responsible for the areas of development in a) virtual and augmented reality interfaces [1,2,6,8,16,19,20] (immersive and nonimmersive virtual environments) associated with adapted physical activity and context physical and neurofunctional rehabilitation; b) wearable devices for sensing and body recognition associated with the control of virtual environments [3,7,9,12,14,15] (from gestural interaction) and; c) movement analysis solution to quantify the functional evolution and describe the motor behaviour associated with gestural interaction [4,5,17] (KinesiOS software). Figure 2 presents the environment's set-up for carrying out the tests.…”
Section: Introductionmentioning
confidence: 99%
“…Such initiatives include developing gesture recognition technologies from computer vision (body scanner) and sensing technologies (ultrasound and inertial units) (Figure 3). They aim to control (by gestural interaction) augmented and virtual reality interfaces with gerontology [13] (mental health) applications and neurofunctional recovery therapies [2,8,10,11,18] not limited to those specialities or pathologies. Also, contributing to training kinesiology specialists with assistive technologies related to virtual reality, especially in physiotherapy, occupational therapy, physical education and medicine (orthopaedics and physiatrics) courses.…”
Section: Introductionmentioning
confidence: 99%